Administrator's report on transport - Farr, Frank
1936-11-15 041-0012-001 ADMINISTRATOR'S REPORT ON TRANSPORT. I enclose with this a complete dossier on transport which has been supplied from various sources. Apart from the information of a psychological nature it gives there is one basic element to be discovered and that is dissatisfaction. The following remarks consist of what I deem to be both fair and true from the reports of individual workers together with my own observations. I have also tried to consider the Committee's pocket. The transport which we have at Granen does not consist of ambulances but medium-weight (2-ton) commercial vehicles. The big Renaults are not independently sprung therefore the whole body moves at the slightest road shock, except when under a two-ton load which they never are. The springing does not come into proper operation until the van is fully loaded. The engines are of inferior manufacture and the ratio of power to body weight is insufficient. An attempt has been made to compensate for this in the gear box which for reasons which are obscure to me, is said to be leading to disaster. The two big trucks which are fitted with stretcher mountings are extremely difficult to use since the top berth is quite out of reach of the average tall Spaniard standing on the ground. (Through the fault of no one present a patient was dropped when her stretcher was being removed from an upper berth). The actual mounting is subject to a sway and vibration which besides inconveniencing the patient will probably lead to its breaking adrift. The hoods are permeable to both rain and cold. Having myself spent a night in one of the new vehicles while in service I can testify to almost unbelievable discomfort from wind and cold. There are no clutch-stops and so frequent changing necessitated by low engine power is made the more difficult; when changing up on a slight incline the trucks lose a great deal of way since the wait between third and top is about fifteen seconds. Neither the medical authorities nor the Parc Movil are very impressed by these new additions and they show up very poorly beside Spanish ambulances. I would like to say, however, that they are an improvement on our original transport and certainly better than the second-hand vehicles which were last sent. In explanation of the strength of this report and the others here enclosed I would refer you to my medical report Section "Role of the Hospital". "PRELIMINARY REPORT ON UNIT TRANSPORT". On arrival in Barcelona I received reports that (a) transport had completely collapsed, and (b) there was serious unemployment amongst drivers. These two statements I hold to be completely irreconcilable. On arrival at Granen I found servicable transport to be in a bad condition. In addition there was one truck completely unservicable and one small ambulance running but not fit for active service. These two have since been sent to Sarinena for repair. An instance of irresponsibility in handling the transport was early afforded when the chief mechanic immediately leaped into one of the new ambulances and prepared to use it for transporting a load of washing. Another instance is that of the truck in bad condition. 292/946/41/12(i)